IL-1β and TNFα Promote Monocyte Viability through the Induction of GM-CSF Expression by Rheumatoid Arthritis Synovial Fibroblasts - Darrieutort-Laffite, Christelle; Boutet, Marie-Astrid; Chatelais, Mathias; Brion, Régis; Blanchard, Frédéric; Heymann, Dominique; Le Goff, Benoit (Mediators of Inflammation, 2014)
Background. Macrophages and synovial fibroblasts (SF) are two major cells implicated in the pathogenesis of rheumatoid arthritis (RA). SF could be a source of cytokines and growth factors driving macrophages survival and activation. Here, we studied the effect of SF on monocyte viability and phenotype. Methods. SF were isolated from synovial tissue of RA patients and CD14+ cells were isolated from peripheral blood of healthy donors. SF conditioned media were collected after 24 hours of culture with or without stimulation with TNFα or IL-1β. Macrophages polarisation was studied by flow cytometry. Results. Conditioned medium from SF significantly increased monocytes viability by 60% compared to CD14+ cells cultured in medium alone (P<0.001). This effect was enhanced using conditioned media from IL-1β and TNFα stimulated SF. GM-CSF but not M-CSF nor IL34 blocking antibodies was able to significantly decrease monocyte viability by 30% when added to the conditioned media from IL-1β and TNFα stimulated SF (P<0.001). Finally, monocyte cultured in presence of SF conditioned media did not exhibit a specific M1 or M2 phenotype. Conclusion. Overall, rheumatoid arthritis synovial fibroblasts stimulated with proinflammatory cytokines (IL-1β and TNFα) promote monocyte viability via GM-CSF but do not induce a specific macrophage polarization.